Ecological Energetic Perspectives on Responses of Nitrogen-Transforming Chemolithoautotrophic Microbiota to Changes in the Marine Environment - Dang, Hongyue; Chen, Chen-Tung A. (Frontiers in Microbiology, 2017)
Transformation and mobilization of bioessential elements in the biosphere, lithosphere, atmosphere, and hydrosphere constitute the Earth’s biogeochemical cycles, which are driven mainly by microorganisms through their energy and material metabolic processes. Without microbial energy harvesting from sources of light and inorganic chemical bonds for autotrophic fixation of inorganic carbon, there would not be sustainable ecosystems in the vast ocean. Although ecological energetics (eco-energetics) has been emphasized as a core aspect of ecosystem analyses and microorganisms largely control the flow of matter and energy in marine ecosystems, marine microbial communities are rarely studied from the eco-energetic perspective. The diverse bioenergetic pathways and eco-energetic strategies of the microorganisms are essentially the outcome of biosphere-geosphere interactions over evolutionary times. The biogeochemical cycles are intimately interconnected with energy fluxes across the biosphere and the capacity of the ocean to fix inorganic carbon is generally constrained by the availability of nutrients and energy. The understanding of how microbial eco-energetic processes influence the structure and function of marine ecosystems and how they interact with the changing environment is thus fundamental to a mechanistic and predictive understanding of the marine carbon and nitrogen cycles and the trends in global change. By using major groups of chemolithoautotrophic microorganisms that participate in the marine nitrogen cycle as examples, this article examines their eco-energetic strategies, contributions to carbon cycling, and putative responses to and impacts on the various global change processes associated with global warming, ocean acidification, eutrophication, deoxygenation, and pollution. We conclude that knowledge gaps remain despite decades of tremendous research efforts. The advent of new techniques may bring the dawn to scientific breakthroughs that necessitate the multidisciplinary combination of eco-energetic, biogeochemical and “omics” studies in this field.